Methods for Measurement and Statistical Analysis of the Frangibility of Strengthened Glass - Tang, Zhongzhi; Mauro, Yihong Z.; Gee, Christopher; Duffy, Delena L. J.; Meyer, Timothy E.; Abrams, Matthew B.; Walker, Kimberly A.; Mauro, John C. (Frontiers in Materials, 2015)
Chemically strengthened glass features a surface compression and a balancing central tension (CT) in the interior of the glass. A greater CT is usually associated with a higher level of stored elastic energy in the glass. During a fracture event, release of a greater amount of stored energy can lead to frangibility, i.e., shorter crack branching distances, smaller fragment size, and ejection of small fragments from the glass. In this paper, the frangibility and fragmentation behaviors of a series of chemically strengthened glass samples are studied using two different manual testing methods and an automated tester. Both immediate and delayed fracture events were observed. A statistical method is proposed to determine the probability of frangible fracture for glasses ion exchanged under a specific set of conditions, and analysis is performed to understand the dependence of frangibility probability on sample thickness, CT, and testing method. We also propose a more rigorous set of criteria for qualifying frangibility.